Genetic Studies of Acute Tolerance, Rapid Tolerance, and Drinking in the Dark in the LXS Recombinant Inbred Strains. (24th July 2013) - Radcliffe, Richard A.; Larson, Colin; Bennett, Beth
<x xml:space="preserve">Abstract</x> Background We hypothesized that rapid tolerance (1‐day tolerance) for the duration of the loss of righting reflex ("sleep time" [ST]) was mediated by an increase in acute functional tolerance (AFT). We also hypothesized that increased AFT would correspond to increased drinking. These questions were addressed using the LXS recombinant inbred mouse strain panel. Methods Mice were given a pretreatment dose of either saline or 5 g/kg alcohol on day 1. On day 2, mice were tested for ST (4.1 g/kg) using a method with which it is possible to accurately assess AFT. Genetic correlation analysis was conducted among the ST‐related variables and also with "drinking in the dark" (DID) which was previously measured by Saba and colleagues (2011). Results Saline‐pretreated mice showed a continuous distribution of ST ranging from 40 minutes to over 3 hours. Of the 43 strains tested, 9 showed significantly decreased ST after alcohol pretreatment, while in 3 strains, ST was significantly increased. AFT scores ranged from 0 to over 200 mg% in the saline group, and in the alcohol group, 8 strains showed a significant increase in AFT and 2 strains showed significant decrease in AFT. In the saline group, AFT was significantly correlated with ST (r = −0.47), but not in the alcohol group (r = −0.22). DID was significantly correlated with only AFT in the alcohol pretreated group (r = 0.64). Conclusions The results suggest that AFT is an important component of the overall ST response, but that the alcohol pretreatment–induced change in AFT does not contribute to rapid ST tolerance. The significant correlation between DID and AFT in the alcohol group suggests that AFT may be a more relevant predictor of drinking behavior than the static measurement of ST. Moreover, preexposure to alcohol seems to change AFT in a way that makes it an even stronger predictor of drinking behavior.